(untitled) (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2023)
The objective of this study is to knowing employee compensation, to find out employee motivation and to determine the effect of compensation on employee motivation at PT. PLN Rayon Lakawan, Enrekang Regency. This research used quantitative method with the type of survey research and data colecction techniques using observation, questionnaire and docomentation techniques. The number of population in this study is 50 people or all employees who are at PT. PLN Rayon Lakawan in Enrekang Regency. In addition, the samples were saturated sampling. The questionnaire in this study used a checklist on the place provided. The researcher made a questionnaire where the researchers combined the two variables. The result of this research reveals that compensation offers a sizable influence on employee motivation so that employee motivation is good enough because the compensation given is in accordance with what is given by company to the employee. The Variables Compensation can provide a positive influence on Employee Motivation PT. PLN Rayon Lakawan, Enrekang Regency.